The Role of BUMN in the Papua Region, Critical Perspective (E-Jurnal Akuntansi, 2026)
This research aims to determine the role of BUMN in the Papua Region in its efforts to encourage the government as an economic actor and has the aim of providing goods and services for the community. This research also aims to find out about the potential of natural resources and products from the Papua Province which can be used as investment supporting factors. This research uses a qualitative research method with a case study approach. Data collection was carried out by means of literature study and documentation. The results of this research show that BUMN in the Papua region has a very important role and function in increasing investment growth and the community economy, especially local investment which has good investment opportunities. The contributions in this research are theoretical contributions, practical contributions and policy contributions. In accordance with the existing reality or facts, this research can provide input and become an information reference for the performance of State-Owned Enterprises (BUMN), as well as providing equal opportunities for local businesses to participate in investing, especially contributing to the regional economy.
Keywords: BUMN; Government; Investment; Economy